Analysis of innovativeness, as a determinant of competitiveness of the selected European countries - Despotovic, Danijela Z; Cvetanović, Slobodan; Nedic, Vladimir (Industrija, 2016)
Starting from the premise that the phenomenon of innovation is at the heart of modern economic policies, the focus of the paper is on the most innovative and least innovative European countries, based on the values of the 12th pillar of the Global Competitiveness Index (GCI) – Innovation. The research centres on the analysis of the selected countries, observing them as 10 innovation leaders and 10 innovation learners of Europe in 2013. Cluster analysis of the selected countries shows the depth of the gap between the formed clusters of innovation leaders and innovation learners. By applying the method of visualisation, the paper examines the components of the pillar Innovation in respect of these countries. With regard to the clusters formed and a big difference between them, the further course of the research includes the time dimension and analyses the trend of innovativeness in the studied groups of countries for the period 2006 - 2015. The time series graphs for each of the clusters, according to indicators of Innovation, with average values per cluster have been constructed, showing also the trend lines for each of the clusters. Bearing in mind that the majority of macroeconomic time series exhibits time dependence, dynamic relations between them are analysed using the VAR model. Statistically significant interdependence is established between the observed series. Furthermore, through simple linear regression, the impact of innovativeness on GDP per capita of the observed group of countries is examined. It can be concluded that, in addition to the pronounced gap between the achieved levels of innovativeness of the observed groups of countries, there is a positive impact of innovativeness on the achieved level of GDP per capita, expressed in the purchasing power of the domestic currency on the part of the group of innovation “learners” in the reporting time period.
Keywords: Innovativeness; Divergence; Learners; Leaders; Innovation; Europe